Development and Validation of the Whole Atmosphere Community Climate Model With Thermosphere and Ionosphere Extension (WACCM‐X 2.0). (9th February 2018) - Liu, Han‐Li; Bardeen, Charles G.; Foster, Benjamin T.; Lauritzen, Peter; Liu, Jing; Lu, Gang; Marsh, Daniel R.; Maute, Astrid; McInerney, Joseph M.; Pedatella, Nicholas M.; Qian, Liying; Richmond, Arthur D.; et al.
Abstract: Key developments have been made to the NCAR Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension (WACCM‐X). Among them, the most important are the self‐consistent solution of global electrodynamics, and transport of O + in the F‐region. Other ionosphere developments include time‐dependent solution of electron/ion temperatures, metastable O + chemistry, and high‐cadence solar EUV capability. Additional developments of the thermospheric components are improvements to the momentum and energy equation solvers to account for variable mean molecular mass and specific heat, a new divergence damping scheme, and cooling by O( 3 P) fine structure. Simulations using this new version of WACCM‐X (2.0) have been carried out for solar maximum and minimum conditions. Thermospheric composition, density, and temperatures are in general agreement with measurements and empirical models, including the equatorial mass density anomaly and the midnight density maximum. The amplitudes and seasonal variations of atmospheric tides in the mesosphere and lower thermosphere are in good agreement with observations. Although global mean thermospheric densities are comparable with observations of the annual variation, they lack a clear semiannual variation. In the ionosphere, the low‐latitude E × B drifts agree well with observations in their magnitudes, local time dependence, seasonal, and solar activity variations. The prereversal enhancement in the equatorial region, which is associated with ionospheric irregularities, displays patterns of longitudinal and seasonal variation that are similar to observations. Ionospheric density from the model simulations reproduces the equatorial ionosphere anomaly structures and is in general agreement with observations. The model simulations also capture important ionospheric features during storms. Plain Language Summary: A comprehensive numerical model, the Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension (WACCM‐X), has been improved, in order to simulate the entire atmosphere and ionosphere, from the Earth's surface to ∼700 km altitude. This new version (v. 2.0) adds the capability to calculate the motions and temperatures of ions and electrons in the ionosphere. The model results compare well with available ground‐based and satellite observations, under both quiet and disturbed space weather conditions. Even with constant solar forcing, the model displays large day‐to‐day weather changes in the upper atmosphere and ionosphere, with basic patterns that agree with observations. This demonstrates the model ability to describe the connections between weather near the surface and weather in space. Key Points: The Whole Atmosphere Community Climate Model has been extended to include ionospheric electrodynamics WACCM‐X simulates the interaction of lower atmosphere and solar influences in the ionosphere Preliminary validation demonstrates agreement with observations